Service Quality and Speed of Service in the Nigeria Police Force: The Roles of SERVICOM - Olowe; Sunday; Ogunode, Temitope; Olatunde, Philips (British Journal of Marketing Studies, 2020)
This paper focused on service quality and speed of service in the Nigeria police force: the role of service compatibility (SERVICOM). The study specifically examined the effect of SERVICOM on the quality of service as well as timeliness of service in the Nigeria police force. Descriptive survey design was adopted through which structured questionnaire was used to collect data from the field. The population of the study comprised of all police officers from all ranks and files within Ekiti and Ondo States as well as consumers of police services. Convenience sampling technique was used to select 4,000 respondents which included 2,000 police officers from different ranks and files as well as 2,000 consumers of police services within the two states. Available data were analysed with the use of descriptive statistics as well as t-test for the formulated hypotheses. Findings showed that SERVICOM, if fully implemented, has significant effect on both quality and timeliness of service in the Nigeria police force. It was therefore recommended among others that an enhanced salary structure which will be globally competitive should be introduced into the Nigeria police force so as to enhance the quality of their services.